Permutation invariant matrix quantum thermodynamics and negative specific heat capacities in large N systems - Denjoe O’Connor; Sanjaye Ramgoolam (Journal of High Energy Physics)
Abstract We study the thermodynamic properties of the simplest gauged permutation invariant matrix quantum mechanical system of oscillators, for general matrix size N. In the canonical ensemble, the model has a transition at a temperature T given by x = e − 1 / T ~ x c = e − 1 / T c = log N N $$ x={e}^{-1/T}\sim {x}_c={e}^{-1/T_c}=\frac{\log N}{N} $$ , characterised by a sharp peak in the specific heat capacity (SHC), which separates a high temperature from a low temperature region. The peak grows and the low-temperature region shrinks to zero with increasing N. In the micro-canonical ensemble, for finite N, there is a low energy phase with negative SHC and a high energy phase with positive SHC. The low-energy phase is dominated by a super-exponential growth of degeneracies as a function of energy which is directly related to the rapid growth in the number of directed graphs, with any number of vertices, as a function of the number of edges. The two ensembles have matching behaviour above the transition temperature. We further provide evidence that these thermodynamic properties hold in systems with U(N) symmetry such as the zero charge sector of the 2-matrix model and in certain tensor models. We discuss the implications of these observations for the negative specific heat capacities in gravity using the AdS/CFT correspondence.